2013
DOI: 10.2147/ijn.s47279
|View full text |Cite
|
Sign up to set email alerts
|

In situ tissue engineering with synthetic self-assembling peptide nanofiber scaffolds, PuraMatrix, for mucosal regeneration in the rat middle-ear

Abstract: Middle-ear mucosa maintains middle-ear pressure. However, the majority of surgical cases exhibit inadequate middle-ear mucosal regeneration, and mucosal transplantation is necessary in such cases. The aim of the present study was to assess the feasibility of transplantation of isolated mucosal cells encapsulated within synthetic self-assembling peptide nanofiber scaffolds using PuraMatrix, which has been successfully used as scaffolding in tissue engineering, for the repair of damaged middle-ear. Middle-ear bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 67 publications
1
43
0
1
Order By: Relevance
“…Immunohistochemistry was performed with the indirect enzyme‐labelled antibody method as described previously . The sections were deparaffinized with toluene and rehydrated with serially graded ethanol solutions and treated with 0.2% TritonX‐100 (Sigma) in PBS.…”
Section: Methodsmentioning
confidence: 99%
“…Immunohistochemistry was performed with the indirect enzyme‐labelled antibody method as described previously . The sections were deparaffinized with toluene and rehydrated with serially graded ethanol solutions and treated with 0.2% TritonX‐100 (Sigma) in PBS.…”
Section: Methodsmentioning
confidence: 99%
“…Insufficient gas exchange in the mastoid mucosa often results in retraction of the tympanic membrane, causing recurrence of otitis media or hearing loss. Akiyama et al isolated mucosal cells from Sprague Dawley transgenic rats, transfected with enhanced green fluorescent protein (EGFP), encapsulated them within the Ac‐(RADA) 4 ‐CONH 2 self‐assembling peptide hydrogel, and transplanted the tissue culture into immunosuppressed rats which had undergone surgical removal of their middle‐ear mucosa . The authors found a significant number of EGFP‐expressing cells in the recipient middle‐ear after transplantation compared with the control (that is, donor cells in culture medium transplanted by injection).…”
Section: Applications Of Self‐assembling Peptide Hydrogels In Tissue mentioning
confidence: 99%
“…Here, mucosal epithelial cells encapsulated in peptide matrix regenerated the damaged mucosa in the middle ear of Sprague Dawley rats. 66 Very recently Uzunalli and coworkers demonstrated that PAs functionalized with YIGSR and RGD induced corneal stroma regeneration in rabbit models. 67 …”
Section: Regeneration In Other Organsmentioning
confidence: 99%